1994
DOI: 10.1115/1.2930436
|View full text |Cite
|
Sign up to set email alerts
|

Subharmonic and Quasi-Periodic Motions of an Eccentric Squeeze Film Damper-Mounted Rigid Rotor

Abstract: When a squeeze-film damper is operated eccentrically, the nonlinear damper forces are no longer radially symmetric and subharmonic and quasi-periodic vibrations may be excited by the rotor unbalance. In this study, the unbalance response of a rigid rotor, supported on an eccentric squeeze film damper, is first approximated by a harmonic series whose coefficients are determined by the collocation method, together with a nonlinear least-square regression. The stability of the resulting periodic solution is then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…In their work, the linearized Reynolds equation was solved by the finite element method and a comparative stability analysis was done. In 1994, Zhao et al [5] investigated nonlinear dynamic behavior of an eccentric squeeze film damper-mounted rigid rotor system. The authors showed that for large values of unbalance and static misalignment, the subharmonic and quasi-periodic motions generated at speeds of more than twice the system critical speed were bifurcated from the unbalance harmonic solution.…”
mentioning
confidence: 99%
“…In their work, the linearized Reynolds equation was solved by the finite element method and a comparative stability analysis was done. In 1994, Zhao et al [5] investigated nonlinear dynamic behavior of an eccentric squeeze film damper-mounted rigid rotor system. The authors showed that for large values of unbalance and static misalignment, the subharmonic and quasi-periodic motions generated at speeds of more than twice the system critical speed were bifurcated from the unbalance harmonic solution.…”
mentioning
confidence: 99%
“…Sykes and Holmes [5] reported experimental observations of sub-harmonic motion in squeeze film bearings and suggested that such motion was a possible precursor of chaotic motion. Zhao et al [6] investigated the sub-harmonic and quasiperiodic motions of an eccentric squeeze film dampermounted rigid rotor system. The authors showed that for large values of the rotor imbalance and static misalignment, the sub-harmonic and quasi-periodic motions generated at speeds of more than twice the system critical speed were bifurcated from the unstable harmonic solution.…”
Section: Introductionmentioning
confidence: 99%
“…Kim and Noah [10] analyzed the bifurcation of a modified Jeffcott rotor using the bearing clearance as the bifurcation parameter. In 1994, Zhao et al [11] investigated the subharmonic and quasi-periodic motions of an eccentric squeeze film damper-mounted rigid rotor system. The authors noted that at large unbalance and static misalignment values, the subharmonic and quasi-periodic motions generated at speeds of more than twice the system critical speed were bifurcated from the unstable harmonic solution.…”
Section: Introductionmentioning
confidence: 99%